Molecular mechanism of L-SP40 peptide and in vivo efficacy against EV-A71 in neonatal mice - Lalani, Salima; Tan, Soon Hao; Tan, Kuan Onn *; Lim, Hui Xuan *; Ong, Kien Chai; Wong, Kum Thong; Poh, Chit Laa * (Elsevier, 2021)
Aims: Enterovirus A71 (EV-A71) is an etiological agent of hand foot and mouth disease (HFMD) and has the potential to cause severe neurological infections in children. L-SP40 peptide was previously known to inhibit EV-A71 by prophylactic action. This study aimed to identify the mechanism of inhibition in Rhabdomyosarcoma (RD) cells and in vivo therapeutic potential of L-SP40 peptide in a murine model. Main methods: A pull-down assay was performed to identify the binding partner of the L-SP40 peptide. Co-immunoprecipitation and co-localization assays with the L-SP40 peptide were employed to confirm the receptor partner in RD cells. The outcomes were validated using receptor knockdown and antibody blocking assays. The L-SP40 peptide was further evaluated for the protection of neonatal mice against lethal challenge by mouse-adapted EV-A71. Key findings: The L-SP40 peptide was found to interact and co-localize with nucleolin, the key attachment receptor of Enteroviruses A species, as demonstrated in the pull-down, co-immunoprecipitation and co-localization assays. Knockdown of nucleolin from RD cells led to a significant reduction of 3.5 logs of viral titer of EV-A71. The L-SP40 peptide demonstrated 80% protection of neonatal mice against lethal challenge by the mouse-adapted virus with a drastic reduction in the viral loads in the blood (~4.5 logs), skeletal muscles (1.5 logs) and brain stem (1.5 logs). Significance: L-SP40 peptide prevented severe hind limb paralysis and death in suckling mice and could serve as a potential broad-spectrum antiviral candidate to be further evaluated for safety and potency in future clinical trials against EV-A71